Penerapan Sistem Inventaris Aset Desa Berbasis Website di Budugsidorejo Kecamatan Sumobito kabupaten Jombang - Miftachul Chusnah; Muhamad Husnun Ni`an; Golan Iruretta Dewangga; Ahmad Maulana Fajar; Mamluk Ahtul Hidayah (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
Village asset management is an essential component in supporting development and community services. However, manual practices often lead to limited access, data loss, and lack of transparency. This community service program aimed to modernize asset governance through the implementation of a web-based inventory system in Budugsidorejo Village. The main objective was to improve the efficiency of recording processes, provide accurate data, minimize risks of errors, and strengthen transparency for the community. The implementation process involved field analysis, system design, web application development, socialization with village officials, and training sessions to ensure optimal use of the system. The developed platform features asset data recording, centralized storage, tiered access rights, and automated reporting, all designed to support administrative and reporting needs. The results indicate that village officials are now able to manage inventory data more effectively and systematically, while reporting processes have become faster and easier. Furthermore, the community can access information more openly, which enhances public trust. The introduction of this system not only improves efficiency in asset management but also reinforces accountability and transparency of the village government as a foundation for sustainable development.